SEMANTIC ANALYSIS OF FIGURATIVE LANGUAGE EXPRESSIONS IN “FEATURE” OF THE JAKARTA POST - Tri Rohani; Safnil Arsyad (JOALL (Journal of Applied Linguistics and Literature), 2018)
This study aims at investigating the types of figurative lexicons and the types of meaning of figurative lexicons found in “feature” of The Jakarta Post’s December editions. The methodology of the research used descriptive qualitative content analysis. The findings related to research questions showed that there were thirteen types of figurative lexicons found in “feature” of The Jakarta Post and the most dominant type of figurative lexicon found was simile while for the types of meanings of figurative lexicons found in “feature” of The Jakarta Post, it was found that there were seven types of meanings found in “feature” of the Jakarta Post and the most type of meaning of figurative lexicons found was conceptual meaning.  This means that using simile and conceptual meaning in the news presentation of “feature” in The Jakarta Post were effective in order to help the readers easier in understanding the news presented in The Jakarta Post. Therefore, it is then recommended that teachers can bring this type of authentic material to school so the students are motivated and encourged to learn more things in English especially about figurative language and types of meanings